Differentiating Electromechanical From Non-Electrical Substrates of Mechanical Discoordination to Identify Responders to Cardiac Resynchronization Therapy - Lumens, Joost; Tayal, Bhupendar; Walmsley, John; Delgado-Montero, Antonia; Huntjens, Peter R; Schwartzman, David; Althouse, Andrew D; Delhaas, Tammo; Prinzen, Frits W; Gorcsan, 3rd, John (Circulation. Cardiovascular imaging, 2015)
Left ventricular (LV) mechanical discoordination, often referred to as dyssynchrony, is often observed in patients with heart failure regardless of QRS duration. We hypothesized that different myocardial substrates for LV mechanical discoordination exist from (1) electromechanical activation delay, (2) regional differences in contractility, or (3) regional scar and that we could differentiate electromechanical substrates responsive to cardiac resynchronization therapy (CRT) from unresponsive non-electrical substrates. First, we used computer simulations to characterize mechanical discoordination patterns arising from electromechanical and non-electrical substrates and accordingly devise the novel systolic stretch index (SSI), as the sum of posterolateral systolic prestretch and septal systolic rebound stretch. Second, 191 patients with heart failure (QRS duration ≥120 ms; LV ejection fraction ≤35%) had baseline SSI quantified by automated echocardiographic radial strain analysis. Patients with SSI≥9.7% had significantly less heart failure hospitalizations or deaths 2 years after CRT (hazard ratio, 0.32; 95% confidence interval, 0.19-0.53; P<0.001) and less deaths, transplants, or LV assist devices (hazard ratio, 0.28; 95% confidence interval, 0.15-0.55; P<0.001). Furthermore, in a subgroup of 113 patients with intermediate electrocardiographic criteria (QRS duration of 120-149 ms or non-left bundle branch block), SSI≥9.7% was independently associated with significantly less heart failure hospitalizations or deaths (hazard ratio, 0.41; 95% confidence interval, 0.23-0.79; P=0.004) and less deaths, transplants, or LV assist devices (hazard ratio, 0.27; 95% confidence interval, 0.12-0.60; P=0.001). Computer simulations differentiated patterns of LV mechanical discoordination caused by electromechanical substrates responsive to CRT from those related to regional hypocontractility or scar unresponsive to CRT. The novel SSI identified patients who benefited more favorably from CRT, including those with intermediate electrocardiographic criteria, where CRT response is less certain by ECG alone.